Pendampingan Pembuatan Aplikasi Pencatatan Proses Bisnis Menggunakan Vba Macro Excel Pada Apotek Srandakan - Umam, M. Sulkhanul; Nugrahani, Tri Siwi (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Technological developments lead to competition in the business world is no exception in the field of health, namely pharmacies. Pharmacies must be able to survive amid the existing business competition and regulations by optimizing business processes. But in Srandakan Farma Pharmacy recording business processes are still done manually on paper work of vulnerable missing or damaged. This causes the decision making process to be slow. the purpose of service activities is to provide assistance in making applications for recording business processes using Ms. Excel at the Pharmacy Srandakan Farma by utilizing the Visual Basic for Application (VBA) feature. The method of service activities is carried out by observation, training and assistance as well as evaluation to ensure that the application can be properly adopted. Based on the service activities that have been carried out, the application makes recording more structured, information can be available quickly when needed as a basis for decision making. Applications make business processes it easy for owners and employees of pharmacies to carry out a more optimal recording process.